Effect of Carbonation on Microstructure of Cement Pastes with Different Water-to-Cement Ratios - Kopitha, K.; Krishnya, S.; Elakneswaran, Y.; Kitagaki, Y.; Yoda, Y.; Tsujino, M.; Nishida, A. (Springer, 2023)
The durability of the structures is the main concern in the field of engineering. Reinforcement corrosion is the most common cause of concrete structural deterioration. Corrosion of reinforcement results primarily from chloride ingress and carbonation. Cementitious materials are prone to carbonation as carbon dioxide is present everywhere in the atmosphere. For the durability prediction of cement-based materials, it is crucial to know the effect of carbonation on the microstructure of the cement matrix. This study examines how carbonation affects the microstructure of cement paste made up of Ordinary Portland Cement (OPC) with waterto-cement ratios (w/c) of 0.3, 0.4, and 0.5 with the help of the experiments and the newly developed model predicting the hydration products and porosity of the cement paste during the CO2 gas diffusion. As part of this study, phenolphthalein was used to determine the carbonation depth. In addition to identifying the hydrated and carbonated products using X-Ray Diffraction (XRD) and Thermal Gravimetric Analysis (TGA), changes in microstructure were detected through Scanning Electron Microscope (SEM). Furthermore, the microstructures of cement paste samples that have been exposed to 5% carbon dioxide concentration for four months were compared. Carbonation products consist predominantly of calcite type polymorph of calcium carbonate, as revealed by XRD. Portlandite and C-S-H get carbonated simultaneously and the carbonation reaction increases with the increasing w/c in accordance with XRD and TGA results. Eventually, the experimental results of calcite and portlandite were compared with the predicted results from a newly developed COMSOL-IPHREEQC interface, and a better prediction of the numerical model was observed
Keywords: Durability; Carbonation; Microstructure; COMSOL-IPHREEQC